Urothelial cancers of the bladder in young people - Živković Slađana; Veličković Ljubinka; Tasić-Dimov Desanka; Kostov Miloš; Stojanović Nebojša (Vojnosanitetski Pregled)
Tumors of the bladder, particularly urothelial carcinoma (UC) are very rare malignant diseases in young people. They mostly occur in elder persons of male gender. We present 8 patients below 35 years of age, (average age 24.7) in whom the presence of UC was verified. The main symptom was total or terminal hematuria. The results showed that 5 patients had low-risc group of tumors (G1, pTa), while 3 tumors were of medium-risk group (G2, pT1). We concluded that UC in young people was low-grade and non-invasive. However for better evaluation it was neccessary to observe patients for longer period of time.